Schutzian Phenomenology and Hermeneutic Traditions
VI, 281 p.
Keywords: Schutzian Phenomenology and Hermeneutic Traditions links Alfred Schutz to the larger hermeneutic tradition in Continental thought, illuminating the deep affinity between Schutzian phenomenology and hermeneutics. The essays collected here explore a broad spectrum of Schutzian themes and concerns, from Schutz’s concrete affinities to hermeneutic traditions, his interpretationism and the pragmatist nature of Schutz’s thought, to questions concerning the role of the media and music in our understanding of the life-world and intersubjectivity. The essays go on to explore the practical applicability of Schutz’s thoughts on questions regarding economics, literature, ethics and the limits of human understanding. Given its emphasis on the application of Schutzian ideas and concepts, this book willbe of special interest to a wide range of readers in the social sciences and humanities, who are interested in the application of phenomenology to social, political, and cultural phenomena.